1989
DOI: 10.1164/ajrccm/140.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 Receptor Gene Expression by Bronchoalveolar Lavage Lymphocytes in Pulmonary Sarcoidosis

Abstract: Current concepts of the immunopathogenesis of sarcoidosis favor a central role of activated, interleukin-2 (IL-2) producing helper T-cells at sites of inflammation. Normally, activated T-cells release IL-2 and express IL-2 receptors (IL-2R). IL-2R+ cells, however, are not uniformly found in patients with clinically active disease. To determine whether the lack of IL-2R+ cells is caused by a dysregulation of the IL-2R gene or by the mode of T-cell activation in pulmonary sarcoidosis, we quantified IL-2 and IL-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…In spite of the systemic nature of the disease only the alveolar T-cells and not those of the peripheral blood spontaneously secreted IL-2. Interestingly, the regulation of the transcription of the IL-2 gene appeared to be normal, indicating a stimulation of the cells in a physiological fashion [88,137]. This view is supported by the finding of DU BOIS et al [138], who demonstrated a capping of the TCR of alveolar Tcells in sarcoidosis, suggesting a recent activation of the cells via this complex.…”
Section: T-cellsmentioning
confidence: 87%
See 2 more Smart Citations
“…In spite of the systemic nature of the disease only the alveolar T-cells and not those of the peripheral blood spontaneously secreted IL-2. Interestingly, the regulation of the transcription of the IL-2 gene appeared to be normal, indicating a stimulation of the cells in a physiological fashion [88,137]. This view is supported by the finding of DU BOIS et al [138], who demonstrated a capping of the TCR of alveolar Tcells in sarcoidosis, suggesting a recent activation of the cells via this complex.…”
Section: T-cellsmentioning
confidence: 87%
“…In some cases of sarcoidosis >50% of T-cells with a CD4/CD8 ratio >10 which exhibit markers of activation, such as increased HLA-DR, very late activation antigen-1 (VLA-1), and IL-2 receptor expression and capping of the T-cell antigen receptor (TCR), can be observed [4,[135][136][137][138]. The Tcells of the granuloma exhibit a layer-like distribution, with CD4+ cells expressing an abundance of activation markers predominantly in the inner area and an accumulation of CD8+ cells with smaller numbers of those markers in the outer area [139,140].…”
Section: T-cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…We now conclude that most lung lymphocytes are in fact probably very recently reactivated cells, as CD69 expression peaks at 18-24 hours and decays with a half-life of 24 hours (28) , and CD25 surface expression persists for only a few days after lymphocyte activation in vitro (29) . Significant expression of CD25 by lung lymphocytes is a feature of several human immunologic lung diseases (30)(31)(32) . Because the vast majority of lymphocytes at any site of inflammation are not specific for the inciting antigens, it is unlikely that the high percentage of CD25+ cells results from lymphocyte activation within lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Bronchoalveolar lavage (BAL) studies have disclosed prominent activation of alveolar macrophages and T cells, with a predominant Th1 cytokine profile. 10,11 The inflammatory response is characterized by increased production of proinflammatory cytokines, including interleukin (IL)-2, interferon (IFN-g), tumour necrosis factor (TNF)-a, interleukin IL1b, interleukin (IL)-6, and chemokines that amplify the inflammatory process and recruit monocytes from the periphery. [12][13][14][15][16][17] Cytokine gene expression is regulated via several mechanisms.…”
Section: Introductionmentioning
confidence: 99%